Internalization of Gapura Pancawaluya Values through Community Based Creative Dance Learning in Angklung Sered Balandongan - Rivaldi Indra Hapidzin; Trianti Nugraheni; Tati Narawati; Agus Ahmad Wakih (ARRUS Journal of Social Sciences and Humanities, 2026)
Community-based dance learning plays an important role in character education and the strengthening of cultural identity. This study aims to examine the pedagogical process, representations of cultural values, and the learning implications of Creative Dance in Angklung Sèrèd Balandongan within a community context. The research employed a qualitative case study approach grounded in ethnopedagogy and was conducted in Balandongan Village, Tasikmalaya, with data collected through participant observation, in-depth interviews, and documentation across different age groups. The findings indicate that the learning of Creative Dance in Angklung Sèrèd Balandongan functions as a socio-cultural learning ecosystem that integrates embodied experience, the symbolic meanings of dance properties, and local Sundanese values. Aesthetic transformation is reflected in the development of movement quality and expressive engagement among participants, while the internalization of the Gapura Pancawaluya values cageur, bageur, bener, pinter, singer, and pangger is realized through the symbolic interpretation of the umbrella, kolotok, and Hihid. These findings affirm that community-based creative dance pedagogy contributes significantly to character formation in education and to the sustainability of local culture.